Oscillating holograms recorded in photorefractive crystals by a frequency detuned feedback loop - Freschi, A. A. [UNESP]; Telles, A. C. C.; Frejlich, J.; Donatti, D. A. [UNESP] (American Institute of Physics (AIP), 2009)
We report an optoelectronic feedback loop suitable for generating noise-free interference patterns oscillating at arbitrary waveforms. The technique allows controlling the frequency detuning between the interfering beams through a phase modulator in a closed-loop interferometer. We use the dither signal method and propose a quasisynchronous demodulation scheme to create a phase modulated error signal for driving the loop. The dynamics of the interference fringes is easily controlled by a voltage waveform from a function generator, which is used in association with a time delay circuit for shifting the frequency of the reference signal used for lock-in demodulation. The technique is specially suited for applications involving low-frequency phase oscillations, such as those frequently encountered in the generation of space-charge waves in highly resistive photorefractive materials. The processing scheme allows real time monitoring of the hologram strength, and absolute values for the diffraction efficiency and the holographic phase shift can be obtained. Photorefractive wave oscillations ranging from approximately 100 mHz to 10 Hz were produced in a nominally undoped Bi(12)TiO(20) sample. The technique can be readily applied to other fields of optical interferometry, such as for testing optical surfaces, optimizing adaptive holographic devices, measuring physical quantities, among other applications.
Keywords: bismuth compounds; delay circuits; demodulation; holographic interferometry; optical tuning; phase modulation; photorefractive materials